2007
DOI: 10.1016/j.jadohealth.2007.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Covariation of Adolescent Physical Activity and Dietary Behaviors Over 12 Months

Abstract: The strongest covariation was observed for diet variables that are inherently related (calories and fat, fiber, and fruit/vegetables). Little covariation was detected within or between other diet, physical activity and sedentary behavior domains suggesting that interventions to improve these behaviors in adolescents need to include specific program components for each target behavior of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 39 publications
7
33
0
Order By: Relevance
“…The few longitudinal studies included in the review also indicated an inverse relationship between SB and the intake vegetables [18,34]; and a positive association between TV viewing and the consumption of food items such as snacks and sugar sweetened beverages [35], which is in line with the findings of this study. This study adds to the existing literature by extending these findings to the use of computer/games.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The few longitudinal studies included in the review also indicated an inverse relationship between SB and the intake vegetables [18,34]; and a positive association between TV viewing and the consumption of food items such as snacks and sugar sweetened beverages [35], which is in line with the findings of this study. This study adds to the existing literature by extending these findings to the use of computer/games.…”
Section: Discussionsupporting
confidence: 84%
“…The evidence in support of this hypothesis is however conflicting. Whereas several studies have shown an inverse relationship between screen-based SB and PA [14-17], other studies, including a large meta-analysis indicated that the relationship is weak, making its practical significance limited [2,18-20]. Other studies documented no associations between SB and PA during adolescence [21-24].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment group exemplified significant covariation effects among behavior pairs at each timepoint, meaning that movement to A/M for one behavior increased the likelihood of moving to A/M for another behavior. Using a different methodology and only looking at 12-month data, Rosenberg et al (2007) did not find covariation among similar target behaviors. Our data suggest that synergy among multiple behaviors can allow for a more efficient approach to healthy weight management.…”
Section: Discussionmentioning
confidence: 76%
“…Stemming from this debate, many investigations of health-related behavior have tested whether various health behaviors (ranging from dietary habits to substance abuse) tend to co-vary (Hays et al 1984; Neumark-Sztainer et al 1997; Rosenberg et al 2007). The results of these studies have been mixed, but in general, they have reported that there are multiple classes of behavior which are more or less uncorrelated (e.g., adherence to smoking and exercise prescriptions; Persky et al 2005), but that behavior does co-vary within classes (Neumark-Sztainer et al 1997; Rosenberg et al 2007; Terre et al 1990). These studies tested for co-variation among a variety of health behaviors (e.g., cigarette smoking, drug use, and exercise patterns), but none of these studies addressed the question of whether behavioral indicators of adherence generally co-vary or whether adherence is best conceptualized as being a multi-dimensional construct.…”
Section: Introductionmentioning
confidence: 99%